2022
DOI: 10.3389/fpls.2022.903674
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Study on Geographical Populations of the Multipurpose Species Elsholtzia stauntonii Using Transferable Microsatellite Markers

Abstract: Elsholtzia stauntonii Benth. (Lamiaceae) is an economically important ornamental, medicinal and aromatic plant species. To meet the increasing market demand for E. stauntonii, it is necessary to assess genetic diversity within the species to accelerate the process of genetic improvement. Analysis of the transferability of simple sequence repeat (SSR) markers from related species or genera is a fast and economical method to evaluate diversity, and can ensure the availability of molecular markers in crops with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…There are many methods of studying the population genetics of species, such as using morphological, cellular, biochemical, and molecular markers. These latter three are vulnerable to environmental and other aspects compared with morphological markers [24]. Previous studies have shown that the limited number of SNPs is the main bottleneck limiting the accuracy of kinship estimation [25].…”
Section: Genetic Diversity Analysismentioning
confidence: 99%
“…There are many methods of studying the population genetics of species, such as using morphological, cellular, biochemical, and molecular markers. These latter three are vulnerable to environmental and other aspects compared with morphological markers [24]. Previous studies have shown that the limited number of SNPs is the main bottleneck limiting the accuracy of kinship estimation [25].…”
Section: Genetic Diversity Analysismentioning
confidence: 99%
“…There are many ways to study population genetics of species, such as morphological, cellular, biochemical, and molecular markers. Compared with morphological markers, they are vulnerable to environmental and other factors [20]. Cell markers are relatively time-consuming and laborious; biochemical markers are prone to tissue differences; and molecular markers have certain advantages [21].…”
Section: Genetic Diversity Analysismentioning
confidence: 99%
“…Consequently, it is anticipated that phylogenetically related taxa will exhibit a greater likelihood of success in achieving amplification due to their closer genetic relationships and more similar genomic structures [8,9]. Heterologous amplification has been extensively applied across a broad spectrum of plant species, at intergeneric (e.g., [10][11][12][13][14]) and infrageneric levels (e.g., [15][16][17]). As expected, the greatest success in terms of using cross-amplification was found when applying this approach at the infrageneric level (success rate of about 60% [8]).…”
Section: Introductionmentioning
confidence: 99%